TorakochirurgiaLarge vessels and heart traumas as the result of blunt or penetrating injuries to a chest - Dobosz, Jolanta; Gawrychowski, Jacek; Loska, Piotr; Czyżewski, Damian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Introduction: Large vessels and heart traumas cause significant life risk and constitute a serious treatment problem. Such traumas appear much more frequently as the consequence of penetrating injuries, rather than direct or indirect injuries of a chest. Aim: The aim of this dissertation is presenting my own experience in treating 15 patients with artery, vein or heart traumas as the consequence of chest injury. Material and methods: 15 patients, aged 18 to 49, has undergone emergency operations. In three patients, the continuity of left infraclavicular artery was broken, in one patient, the infreclavicular artery and the fourth left intercostal artery were completely severed, in the fifth patient, the right infraclavicular artery was ruptured, the sixth patient had an incised wound of aortic arch between brachiocephalic trunk and common carotid artery. In three cases, the continuity of infraclavicular artery was restored by stitching them end-to-end, in one patient, saphenous vein graft was stitched in, and one patient had a Gore-Tex vascular prosthesis vein graft stitched in. The puncture wound of aorta, 1 cm long, was stitched with single stitches strengthened with fascial flaps. One patient was operated because of a total severing of the right internal thoracic artery, the other because of the cutting of the internal thoracic artery and incised wound of the right vestibule. In those patients, internal thoracic artery was ligated, heart vestibule and damaged lung were stitched. Three patients were operated because of the superior caval vein trauma, including two patients with incised wound of front and back wall, and one because of gunshot wound (pellet) with anterograde heart tamponade. The walles of the damaged caval veins were stitched with continuous sutures. The remaining four patients were operated because of the incision wound of left heart vestibule in two cases, and the third patient was operated because of the incision wound of the auricle of the left vestibule and damage to the left pulmonary artery in interlobular fissure, and the fourth patient because of the ripped left upper pulmonary artery in consequence of the blunt injury of the chest. Results: 14 patients survived, one patient with pulmonary artery trauma, resuscitated during anesthesia. Conclusion: Proper and quick treatment, especially in the case of patients with multiorgan traumas may substantially influence the decrease in the per cent of deaths in consequence of large vessels traumas.